2023
DOI: 10.1051/0004-6361/202346102
|View full text |Cite
|
Sign up to set email alerts
|

A global view on star formation: The GLOSTAR Galactic plane survey

Y. Gong,
G. N. Ortiz-León,
M. R. Rugel
et al.

Abstract: Context. Cygnus X is one of the closest and most active high-mass star-forming regions in our Galaxy, making it one of the best laboratories for studying massive star formation. Aims. We aim to investigate the properties of molecular gas structures on different linear scales with the 4.8 GHz formaldehyde (H2CO) absorption line in Cygnus X. Methods. As part of the GLOSTAR Galactic plane survey, we performed large-scale (7º×3º) simultaneous H2CO (11,0–11,1) spectral line and radio continuum imaging observations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 137 publications
0
4
0
Order By: Relevance
“…The column density of H 2 CO in the upper energy level, N u , may be estimated from the total H 2 CO column density N tot . For the H 2 CO (1 10 −1 11 ) absorption in the H II region of Cygnus X, Gong et al (2023) adopted an empirical relation between N u and N tot : N u /N tot ; 0.39 for a representative kinetic temperature of 10 K. This ratio may be different for different regions, but it should not vary too much under similar physical conditions. While there can be a 13% uncertainty in the derived column densities based on the above empirical relation, we have estimated the uncertainty in T ex caused by this 13% uncertainty using Monte Carlo simulations and found that the uncertainty in T ex is less than 0.1 K.…”
Section: The Methods Of Calculating the Excitation Temperaturementioning
confidence: 99%
See 2 more Smart Citations
“…The column density of H 2 CO in the upper energy level, N u , may be estimated from the total H 2 CO column density N tot . For the H 2 CO (1 10 −1 11 ) absorption in the H II region of Cygnus X, Gong et al (2023) adopted an empirical relation between N u and N tot : N u /N tot ; 0.39 for a representative kinetic temperature of 10 K. This ratio may be different for different regions, but it should not vary too much under similar physical conditions. While there can be a 13% uncertainty in the derived column densities based on the above empirical relation, we have estimated the uncertainty in T ex caused by this 13% uncertainty using Monte Carlo simulations and found that the uncertainty in T ex is less than 0.1 K.…”
Section: The Methods Of Calculating the Excitation Temperaturementioning
confidence: 99%
“…Of course, the ratio of column densities between H 2 CO and H 2 may not be equal everywhere, and the ratio of column densities between H 2 CO and 13 CO may also not be equal everywhere. These variations could introduce uncertainty in the H 2 CO column density, which may vary by about an order of magnitude (Gong et al 2023;Tang et al 2018). For some representative values of T L , T c and ΔV, we can describe how T ex and τ vary with changing N u , as shown in Figure 2.…”
Section: The Methods Of Calculating the Excitation Temperaturementioning
confidence: 99%
See 1 more Smart Citation
“…The integral velocity interval is [−100, 40] km s −1 . Around the center of the Cygnus X region (the Cyg OB2 cluster), there are many bright filamentary molecular clouds, and a lot of research has focused on these molecular clouds over the past few decades (e.g., Schneider et al 2010;Cao et al 2022;Gong et al 2023;Li et al 2023). However, the relatively isolated L914 molecular cloud located at the periphery of this region has received little attention.…”
Section: L914: a Filamentary Molecular Cloud With Striationsmentioning
confidence: 99%